2023
DOI: 10.3389/fendo.2023.1094075
|View full text |Cite
|
Sign up to set email alerts
|

Association between body fat and sarcopenia in older adults with type 2 diabetes mellitus: A cross-sectional study

Abstract: ObjectivesTo investigate the association between body fat (BF%) and sarcopenia in older adults with type 2 diabetes mellitus (T2DM) and potential link with increased levels of inflammatory indicators and insulin resistance.MethodsA total of 543 older adults with T2DM were included in this cross-sectional study. Appendicular skeletal muscle (ASM), handgrip strength and gait speed were measured to diagnose sarcopenia according to the updated Asian Working Group for Sarcopenia (AWGS) 2019 criteria. Body compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…This study identified high WWI as a significant risk factor for sarcopenia. Past research suggested that high BMI was a protective factor for sarcopenia [26][27][28][29] , while high body fat percentage was a risk factor 28,30,31 . Although these indices indicate a higher degree of obesity as they increase in value, the observed results are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…This study identified high WWI as a significant risk factor for sarcopenia. Past research suggested that high BMI was a protective factor for sarcopenia [26][27][28][29] , while high body fat percentage was a risk factor 28,30,31 . Although these indices indicate a higher degree of obesity as they increase in value, the observed results are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…We defined low physical activity as ≤5 METs by the Duke index, with the mean being lower in subjects with sarcopenia; however, in the multivariate analysis, it was not associated with the presence of sarcopenia, low muscle strength, low muscle mass, or low gait speed. Nevertheless, several studies have reported that a state of pre-frailty (OR 4.75; 95% CI 1.90-11.89; p = 0.001) [49] and low physical activity (OR 15.35; 95% CI 1.69-139.47; p = 0.015) increases the risk of sarcopenia [19,22,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Amongst T2DM patients, those with incident sarcopenia have worse islet function, insufficient insulin secretion, and more significant blood glucose fluctuations than non-sarcopenic patients [33][34][35][36]. In addition, higher body fat content was associated with sarcopenia in older adults with T2DM [37].…”
Section: Type 2 Diabetes and Sarcopeniamentioning
confidence: 99%